2011
DOI: 10.1016/j.ajpath.2011.01.026
|View full text |Cite
|
Sign up to set email alerts
|

SPLUNC1 Promotes Lung Innate Defense Against Mycoplasma pneumoniae Infection in Mice

Abstract: Short palate, lung, and nasal epithelium clone 1 (SPLUNC1) protein is highly expressed in normal airways, but is dramatically decreased in allergic and cigarette smoke exposure settings. We have previously demonstrated SPLUNC1 in vitro antibacterial property against Mycoplasma pneumoniae (Mp). However, its in vivo biological functions remain unclear. The objectives of this study were to determine the in vivo functions of SPLUNC1 following bacterial (eg, Mp) infection, and to examine the underlying mechanisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 38 publications
5
70
0
Order By: Relevance
“…SPLUNC1 has well-defined antimicrobial properties (16)(17)(18)(19). It blocks microbial invasion in the respiratory tract by inhibiting pathogen growth, and through its surfactant properties inhibits biofilm development (16,19,20,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPLUNC1 has well-defined antimicrobial properties (16)(17)(18)(19). It blocks microbial invasion in the respiratory tract by inhibiting pathogen growth, and through its surfactant properties inhibits biofilm development (16,19,20,24).…”
Section: Discussionmentioning
confidence: 99%
“…It was initially hypothesized to express antimicrobial functions, and has been shown to inhibit the growth of multiple pathogens (16)(17)(18)(19), inhibit biofilm formation, and possess surfactant properties (20,21). Although most studies of SPLUNC1 have focused on these antimicrobial effects, SPLUNC1 also regulates the epithelial sodium channel (ENaC) to maintain airway surface liquid depth, affects mucociliary clearance, and regulates inflammation, thereby limiting allergic airway inflammation (10,(22)(23)(24).…”
mentioning
confidence: 99%
“…We previously demonstrated that the Th2 cytokine IL-13 significantly reduces SPLUNC1 expression and secretion from well-differentiated human primary airway epithelial cells, rendering a host susceptible to bacterial infections (10). Recent studies by our group and others demonstrated that SPLUNC1 is critical for clearing respiratory pathogens such as Mycoplasma pneumoniae and Pseudomonas aeruginosa from murine lungs (10)(11)(12). In addition to its antimicrobial function, we have shown that murine recombinant SPLUNC1 protein inhibits the Toll-like receptor 2 (TLR2) agonist-induced production of IL-8 in human airway epithelial cells (10).…”
mentioning
confidence: 99%
“…(17) SPLUNC1 has also been shown to have an anti-inflammatory function in exogenous microbe-induced respiratory infection, such as K. pneumoniae, (18) Mycoplasma pneumoniae, (19) P. aeruginosa, and Epstein-Barr virus. (20) Additionally, SPLUNC1 could also regulate ion/mucus transport and hydration levels in the lung, (21) lower surface tension by its surfactant-like properties, (22) and act as an inflammatory mediator.…”
Section: Discussionmentioning
confidence: 99%